CHEK2∗1100delC Mutation and Risk of Prostate Cancer - Victoria Hale; Maren Weischer; Jong Y. Park (Prostate Cancer)
Although the causes of prostate cancer are largely unknown, previous studies support the role of genetic factors in the development of prostate cancer. CHEK2 plays a critical role in DNA replication by responding to double-stranded breaks. In this review, we provide an overview of the current knowledge of the role of a genetic variant, 1100delC, of CHEK2 on prostate cancer risk and discuss the implication for potential translation of this knowledge into clinical practice. Currently, twelve articles that discussed CHEK2∗1100delC and its association with prostate cancer were identified. Of the twelve prostate cancer studies, five studies had independent data to draw conclusive evidence from. The pooled results of OR and 95% CI were 1.98 (1.23–3.18) for unselected cases and 3.39 (1.78–6.47) for familial cases, indicating that CHEK2∗1100delC mutation is associated with increased risk of prostate cancer. Screening for CHEK2∗1100delC should be considered in men with a familial history of prostate cancer.